Pengaruh Environmental Knowledge, Green Advertising, dan Environmental Concern terhadap Green Purchase Intention pada Produk Pembalut Kain - Rachela Putri Hanasti; ANDI MUHAMMAD SADAT; ANNISA LUTFIA (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
This study aims to examine the effect of environmental knowledge (EK), green advertising (GA), and environmental concern (EC), on green purchase intention (GPI) on menstrual pad. Respondents are Generation Z women who live in Jakarta, Bandung, Surabaya, Medan, and Makassar. This study uses a quantitative approach through an online survey filled out by 421 respondents and analyzed using SmartPLS 4. The results showed GA and EC are proven to have a positive and significant effect on GPI. However, EK has a negative and insignificant effect on GPI. These findings can be utilized by manufacturers, marketers, government, and environmental organizations to encourage purchase intention towards environmentally friendly products such as menstrual pad.